KAFALAH BI AN NAFS DAN JAMINAN ORANG DALAM PENANGGUHAN PENAHANAN - Hanif Azhar; Patsun (CENDEKIA: Jurnal Studi Keislaman, 2021)
This research is based on the editorial of article 31 paragraphs 1 and 2 of the Criminal Procedure Code (KUHAP) regarding the possibility of a suspension of detention for a suspect or defendant on bail. The phrase "guaranteed people" suggests the meaning of "self-guarantee" which can be understood that if it turns out that the suspect or defendant escapes, the guarantor will replace the suspect or defendant in the legal process. Articles 35 and 36 of PP No. 27 of 1983 concerning the Implementation of the Criminal Procedure Code (KUHAP) makes it clear to this editorial that what is meant by "person guarantees" is ultimately money guarantees as well, but those that come from guarantors, not from suspects or defendants as well as suspension of detention with money guarantees. From here the author wants to study further this provision from the perspective of Islamic law by tracing the literature of Islamic law relating to the guarantee of suspension of detention. The questions that are then asked are: First, what is the mechanism for guaranteeing the suspension of detention with personal guarantees according to the Criminal Procedure Code? Second, what is the perspective of Islamic law on people's guarantees in suspension of detention? Third, what are the similarities and differences between these two legal concepts? This study uses a normative legal research method (juridical normative) with a comparative approach where this approach is carried out to compare two legal issues that have similarities in two different legal systems: positive law and Islamic law. from this study it was concluded that the concept of guarantees of persons in suspension of detention has equivalents in Islamic law. Both are based on the provisions of material law, namely civil in terms of positive law and muamalah in terms of Islamic law. The two aspects of these two legal systems basically have the same goal, namely to enforce material law where law enforcement officers must ensure the implementation of procedural law procedures properly as a form of upholding justice and legal certainty.